(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the problem of identification conformal behavior in youth. The author outlines the content of the concept of conformism and conformality, features of the identification of conformism in the social group. Specifications of the conformal type of personality are specified. The connection of the conformality of the personality with the self-estimation of a person is shown. Socio-phyhological personality peculiarities of the youth have been defined and investigated. It is proved that conformism is a progressive and natural phenomenon of the period of maturation. The empirical study based on the peculiarities of conformal behavior and self-esteem at the age of youth has been run. According to the results of correlation analysis, the existence of an inverse relationship between the indicators of conformal behavior of boys and the level of their self-esteem.